BBC Sex-for-Grades-Report: Nigeria Tertiary Institutions ˜Crisis Management Strategies and Stakeholders Reactions - Israel Ayinla Fadipe; Nuraen Adesola Bakenne (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
Studies have already acknowledged sexual scandals as public relations nightmares of higher institutions of learning. Therefore, we examined the crisis management strategies of Nigerian tertiary institutions and stakeholders reactions after the British Broadcasting Corporations sex-for-grades report. Adopting qualitative research, we analysed 13 available press releases of institutions retrieved from some institutions websites and sampled opinions of 20 stakeholders comprising parents, students and lecturers through a depth interview. We used Coombs theory of crisis response strategies: denial, diminish, rebuild and bolstering as thematic categories. We discovered that the institutions mostly used denial with diminish response strategy to blame societal decadence, scapegoat female students for and downplayed the severity of sexual harassment incidence by the institutions. More so, all the stakeholders distrust the credibility of local media in the reportage of sexual harassment cases. However, female students feel aggrieved that school administrations and national government neglected them for failing to outlaw sexual harassment and severely punish offenders. Therefore, we recommend that considering stakeholders perception of sexual harassment incidence in Nigerian ivory tower, Nigerian higher educational institutions should not adopt denial response strategy for sex scandal cases.